Nursing Care Of Type Ii Diabetes Mellitus Patients - Yestika Saleha, Triya; Cahyati, Yanti; Arifin Hidayat, Unang (Jurnal Kesehatan Mahardika, 2023)
Background: Type II Diabetes Mellitus is a chronic disease with a high prevalence in Indonesia. As nursing care providers, nurses have an essential role in managing patients with type II Diabetes Mellitus. Purpose: Get an overview of the implementation of nursing care in patients with Type II Diabetes Mellitus. Methodology: A case study was conducted on Mrs. D in Dahlia Room  RSUD Ciamis  on 27 - 30 June 2022. Results: The results of the nursing evaluation obtained: ineffective peripheral perfusion, acute pain, nutritional deficits, impaired skin integrity, unstable blood glucose levels, impaired physical mobility, and disturbed sleep patterns are partially resolved, and the risk of hypovolemia has been determined. Conclusion: Nursing care carried out can overcome the problems experienced by patients.